Melatonin-mediated development and abiotic stress tolerance in plants - Pan, Yue; Xu, Xiaoshan; Li, Lei; Sun, Qinglin; Wang, Qiguang; Huang, Huahong; Tong, Zaikang; Zhang, Junhong (Frontiers in Plant Science, 2023)
Melatonin is a multifunctional molecule that has been widely discovered in most plants. An increasing number of studies have shown that melatonin plays essential roles in plant growth and stress tolerance. It has been extensively applied to alleviate the harmful effects of abiotic stresses. In view of its role in regulating aspects of plant growth and development, we ponder and summarize the scientific discoveries about seed germination, root development, flowering, fruit maturation, and senescence. Under abiotic and biotic stresses, melatonin brings together many pathways to increase access to treatments for the symptoms of plants and to counteract the negative effects. It has the capacity to tackle regulation of the redox, plant hormone networks, and endogenous melatonin. Furthermore, the expression levels of several genes and the contents of diverse secondary metabolites, such as polyphenols, terpenoids and alkaloids, were significantly altered. In this review, we intend to examine the actions of melatonin in plants from a broader perspective, explore the range of its physiological functions, and analyze the relationship between melatonin and other metabolites and metabolic pathways.